PENGEMBANGAN APLIKASI MOBILE LEARNING BERBASIS KEBUDAYAAN NASIONAL (BIMAYANA) UNTUK PEMBELAJARAN MATA KULIAH AKUNTANSI KEUANGAN - Iwan Koerniawan; Siti Kholifah (Jurnal Informatika Upgris, 2016)
The purpose of this study is developing mobile learning BIMAYANA for learning financial accounting with valid criteria. This study is a Research and Development. The development of research using a modification of the 4D model into 3D with the define (definition), design (planning), and development (development). mobile learning BIMAYANA financial accounting subject first tested the validation by media experts, subject matter experts and also questionnaire responses of college students. Retrieved scoring average 85.2% validation of subject matter experts, media expert validation 89.2%, 85.2% votes college student responses, so a decent media mobile learning BIMAYANA is used with very good category